Persoalan-Persoalan Kontemporer dalam Ilmu Hukum - Catharina Dewi Wulansari; Yenny Yorisca (Universitas Serang Raya, 2020)
Through science, we generate new knowledge and discovery, become inspired as we coax nature to reveal her myriad secrets and expand our understanding of the physical and living world. Since the beginning of human civilization, science and technology have progressed in a continuous process. As we know, Science is essentially an attempt to help human solve the problem. Increasingly interdisciplinary science is driving many changes. Some disciplines are becoming irrevocably intertwined. Progress in one field of science makes possible progress in seemingly disparate fields, and increasingly the most exciting research problems involve multidisciplinary collaborations, require the use of large-scale research facilities, and use advanced information technology. In the 21st century, legal studies offer equal promise for improving human welfare. The advances that we have made and will be making, especially in understanding human behavior and its very deep origins, will be translated into interventions of diverse sorts that will have a much bigger impact in terms of improving human welfare. Keywords : Science, Legal Studies, 21st Century.